Educating Informal Educators - Alldred, Pam; Howard, Frances (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Educating Informal Educators'' draws on the range of expertise in Higher Education courses across the UK and seeks to emphasise the value of informal education and its values and practices, not only for students of education or informal education but also for society as a whole. This Special Issue seeks to capture the particular pedagogies of youth and community work courses that sustain distinctive informal education practice.